2020
DOI: 10.1186/s13213-020-01551-2
|View full text |Cite
|
Sign up to set email alerts
|

Identification of salt tolerance-related genes of Lactobacillus plantarum D31 and T9 strains by genomic analysis

Abstract: Purpose: The aim of this study was to identify salt tolerance-related genes of Lactobacillus plantarum D31 and T9 strains, isolated from Chinese traditional fermented food, by genomic analysis. Methods: Tolerance of L. plantarum D31 and T9 strains was evaluated at different stress conditions (temperatures, acid, osmolality, and artificial gastrointestinal fluids). Draft genomes of the two strains were determined using the Illumina sequencing technique. Comparative genomic analysis and gene transcriptional anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 62 publications
1
26
0
Order By: Relevance
“…On the contrary, other studies [ 39 , 40 , 41 ] reported the ability of L. plantarum strains to tolerate high (> 8%) NaCl concentrations. The tolerance to high salt concentrations and the ability to control osmotic stress have been recently confirmed [ 28 ], showing excellent growth performance of L. plantarum strains at 5% and 8% of NaCl. The authors observed that L. plantarum strains are equipped, at genomic level, with a complex molecular regulatory network involving genes associated with salt resistance through the recovery of the intracellular ion balance [ 28 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…On the contrary, other studies [ 39 , 40 , 41 ] reported the ability of L. plantarum strains to tolerate high (> 8%) NaCl concentrations. The tolerance to high salt concentrations and the ability to control osmotic stress have been recently confirmed [ 28 ], showing excellent growth performance of L. plantarum strains at 5% and 8% of NaCl. The authors observed that L. plantarum strains are equipped, at genomic level, with a complex molecular regulatory network involving genes associated with salt resistance through the recovery of the intracellular ion balance [ 28 ].…”
Section: Resultsmentioning
confidence: 99%
“…The tolerance to high salt concentrations and the ability to control osmotic stress have been recently confirmed [ 28 ], showing excellent growth performance of L. plantarum strains at 5% and 8% of NaCl. The authors observed that L. plantarum strains are equipped, at genomic level, with a complex molecular regulatory network involving genes associated with salt resistance through the recovery of the intracellular ion balance [ 28 ]. Our study clearly highlights that the growth behavior under stress conditions is strain-specific, especially at 16 °C ( Figure 2 and Table S2 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Other genes enriched on the plasmids from NL mainly include chloride channel protein, calcium-transporting ATPase, magnesium transporter, and Na + /H + antiporter (Table S5). These proteins are involved in functions such as acid resistance, salt tolerance, metal ion homeostasis and oxidative stress tolerance [46][47][48], probably suggesting their contribution to adaptation of NL to dynamic environments.…”
Section: Inorganic Ion Transport and Metabolismmentioning
confidence: 99%
“…Other genes enriched on the plasmids from NL mainly include chloride channel protein, calcium-transporting ATPase, magnesium transporter, and Na+/H+ antiporter (Table S5). These proteins are involved in functions such as acid resistance, salt tolerance, metal ion homeostasis, and oxidative stress tolerance (46), (47), (48), probably suggesting their contribution to adaptation of NL to the dynamic environments.…”
Section: Resultsmentioning
confidence: 99%